1997
DOI: 10.1002/(sici)1098-1136(199705)20:1<59::aid-glia6>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor and nitric oxide production by retinal Müller glial cells from rats exhibiting inherited retinal dystrophy

Abstract: The primary cause of the inherited retinal dystrophy observed in Royal College of Surgeons (RCS) rats is located in the retinal pigmented epithelium, which is unable to phagocytize photoreceptor outer segments. We have demonstrated here that retinal Müller glial (RMG) cells obtained from RCS dystrophic rats and stimulated in vitro with lipopolysaccharide (LPS) and interferon-gamma (IFN-gamma) accumulated higher levels of tumor necrosis factor (TNF) and inducible nitric oxide synthase (NOS II) mRNA and released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…We demonstrated previously that treatment of RMG cells from the rat (Goureau et al, 1994 b ; Cotinet et al, 1997) with IFN‐γ in combination with LPS induced the expression of NOS‐2 and a subsequent large release of NO. A marked increase in levels of nitrites, an oxidation end product of NO, in cell culture medium provided evidence that NO production was also induced in RMG cells from C57BL/6×129SvEv mice exposed for 72 h to IFN‐γ and LPS (Table 1).…”
Section: Neurotoxic Effects Of No Released From Lps/ifn‐γ‐stimulated mentioning
confidence: 98%
See 2 more Smart Citations
“…We demonstrated previously that treatment of RMG cells from the rat (Goureau et al, 1994 b ; Cotinet et al, 1997) with IFN‐γ in combination with LPS induced the expression of NOS‐2 and a subsequent large release of NO. A marked increase in levels of nitrites, an oxidation end product of NO, in cell culture medium provided evidence that NO production was also induced in RMG cells from C57BL/6×129SvEv mice exposed for 72 h to IFN‐γ and LPS (Table 1).…”
Section: Neurotoxic Effects Of No Released From Lps/ifn‐γ‐stimulated mentioning
confidence: 98%
“…In the retina NOS‐2 is expressed in retinal pigmented epithelial, pericytes, and retinal Müller glial (RMG) cells in vitro after stimulation by cytokines (Goureau et al, 1993 a , 1994 a , b ; Liversidge et al, 1994; Sparrow et al, 1994; Chakravarthy et al, 1995; Cotinet et al, 1997). Furthermore, we have reported that NOS‐2 could be expressed in the retina from AIDS patients during cytomegalovirus retinitis (Dighiero et al, 1994) and in the rat retina during endotoxin‐induced uveitis (EIU) (Goureau et al, 1995; Jacquemin et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence indicates that in proliferative gliosis, Müller cells can promote neuronal cell death through the synthesis and secretion of TNF-a (Cotinet et al, 1997;Giaume et al, 2007;LebrunJulien et al, 2009;Tezel et al, 2001), monocyte chemoattractant protein-1 and NO (Cotinet et al, 1997;Giaume et al, 2007). Excess production of NO by Müller cells and the formation of free nitrogen radicals result in protein nitrosylation, which has toxic effects on surrounding neurons.…”
Section: The Important Role Of Müller Cells In Retinal Homeostasis Anmentioning
confidence: 99%
“…Inherited retinal dystrophy results from accumulation of cellular debris in the subretinal space and visual cell degeneration. Cotinet et al (1997) looked at the retinal Muller (astrocyte-like) cell from dystrophic rats and found that they produce abnormal amounts of TNFa and NOS-2 derived NO. As NO can decrease phagocytosis of photoreceptor segments, which underlies this dystrophy, they suggest that NO may disrupt transmission in retinal neurons.…”
Section: Infectionmentioning
confidence: 99%